Social Motor Coordination in Unaffected Relatives of Schizophrenia Patients: A Potential Intermediate Phenotype - Del-Monte, Jonathan; Capdevielle, Delphine; Varlet, Manuel; Marin, Ludovic; Schmidt, Richard C.; Salesse, Robin N.; Bardy, Benoît G.; Boulenger, jean-Philippe; Gély-Nargeot, Marie Christine; Attal, Jérôme; Raffard, Stéphane (Frontiers in Behavioral Neuroscience, 2013)
Intermediate endophenotypes emerge as an important concept in the study of schizophrenia. Although research on phenotypes mainly investigated cognitive, metabolic or neurophysiological markers so far, some authors also examined the motor behaviour anomalies as potential trait-marker of the disease. However, none of them investigated social motor coordination despite the importance of their anomalies in schizophrenia. The aim of this study was thus to determine whether coordination modifications previously demonstrated in schizophrenia are trait-markers that might be associated with the risk for this pathology. Interpersonal motor coordination in 27 unaffected first-degree relatives of schizophrenia patients and 27 healthy controls was assessed using a hand-held pendulum task to examine the presence of interpersonal coordination impairments in individuals at risk for the disorder. Measures of neurologic soft signs, clinical variables and neurocognitive functions were collected to assess the cognitive and clinical correlates of social coordination impairments in at-risk relatives. After controlling for potential confounding variables, unaffected relatives of schizophrenia patients had impaired intentional interpersonal coordination compared to healthy controls while unintentional interpersonal coordination was preserved. More specifically, in intentional coordination, the unaffected relatives of schizophrenia patients exhibited coordination patterns that had greater variability and in which relatives did not lead the coordination. These results show that unaffected relatives of schizophrenia patients also present deficits in intentional interpersonal coordination. For the first time, these results suggest that intentional interpersonal coordination impairments might be a potential motor intermediate endophenotype of schizophrenia opening new perspectives for early diagnosis.